Thermal optimization of intercellular distance in lithium-ion batteries and numerical analysis of the original honeycomb metal integrated battery pack - Karatas, Osman Bedrettin; Sokmen, Kemal Furkan (Elsevier, 2022)
In Lithium-ion batteries, it is necessary to keep the system temperature within an acceptable range to extend the working life. A thermal management system is also required to maintain temperature uniformity. In this study, first, the steady and transient thermal behavior of 18650 Lithium-ion batteries was investigated, and the results were validated. After this, a module design consisting of 14 battery cells was made and the distance intercellular in this module was optimized. A thermal analysis study of the battery pack was carried out for the most suitable layout. In the study, the differences among modules with cell connection distances of 20, 25, 30, 35 and 40 mm were compared in terms of heat transfer and mounting. To calculate heat transfer data, a Computational Fluid Dynamics based program, FLOEFD was used. According to the results obtained from the analyses, it was determined that the distances between cell centers should be 20 mm, or 25 mm in terms of heat transfer and mounting. Additionally, the design of a metal insert with a honeycomb shape inside the plastic enclosure of the module containing 14 battery cells was examined. It was found that the designed metal insert package had a significant effect on lowering the temperature of the batteries. While the open module maximum temperature was 41.89 degrees C, the module maximum temperature in the package dropped to 37.39 degrees C. In addition, effective results were obtained for equal aging. The cell temperature differences were found to be 0.24 degrees C, 0.17 degrees C, and 0.59 degrees C for Aluminum, Copper and Steel, respectively in metal integrated battery pack analyzes.
Keywords: Lithium ion battery; Heat transfer; Optimization; Battery pack; CFD